(untitled) (Acta Scientiarum. Agronomy, 2023)
Brassica spp. production can be negatively affected by clubroot, which is caused by the protozoan Plasmodiophora brassicae Woronin. Most of the information on clubroot control is derived from studies in temperate regions. Here, management strategies were evaluated to reduce broccoli (Brassica oleracea L. var. italica Plenck) crop losses owing to clubroot in tropical mountain regions. The first experiment revealed the effect of green manure from coriander (Coriandrum sativum L.), sunn hemp (Crotalaria juncea L.), sweet corn (Zea mays L.), and spontaneous vegetation (control) associated with broccoli seedlings of 4 different sizes. In the second experiment, the effect of soil amendments (limestone and steel slag) in conjunction with poultry litter (fresh or composted for 45 days) and without poultry litter (control), was assessed. Both field experiments sought to evaluate the disease intensity, plant development (root growth, biomass, and nutrient accumulation), and yield. Sunn hemp and coriander biomass resulted in higher healthy root volumes and dry weights of broccoli. However, such benefits were not derived from corn treatment. Compared to smaller seedlings (10 mL cell and 20 days of age, and 16 mL cell and 24 days of age), the use of larger seedlings (35 mL cell and 28 days of age, and 50 mL cell and 32 days of age) resulted in lower intensity of clubroot and increased the average yield by 143% in summer crops. Steel slag, like limestone, corrected soil acidity and resulted in plant growth; however, clubroot intensity was not significantly affected. Fresh and composted poultry litter increased the percentage of diseased roots compared with the control; however, broccoli yield was not affected by the treatments. Using green manure (sunn hemp or coriander) and well-developed seedlings is recommended as a strategy to reduce losses induced by clubroot during broccoli cultivation.